TiO2 phase-controlled synthesis of Li-La-TiO solid electrolytes for advanced all-solid-state batteries - Minjeong Kim; Wolil Nam; Jihye Seo; Jihyun Park; Seokha Heo; Yuna Hwang; Sang-Soo Chee; Soobeom Lee; Seungchan Cho; Geon−hyoung An; Yangdo Kim; Moonhee Choi (Journal of Asian Ceramic Societies)
This study focused on achieving high ionic conductivity in Li-La-TiO (LLTO) solid electrolyte. To enhance ionic conductivity, the synthesis reaction was optimized by controlling the composite crystal structure of TiO2 at the B-site of the perovskite (ABO3) structured LLTO, incorporating rutile, brookite, and anatase phases. The solid-phase LLTO, synthesized utilizing the core – shell structured composite-phase TiO2 developed in this study for the first time, successfully transformed its crystal structure to β-LLTO (tetragonal to cubic). This resulted in a significant improvement in ionic conductivity (i.e. 1.11 × 10−4 Scm−1). The study findings confirmed that the composite crystal structure TiO2 used in the solid-phase synthesis of LLTO induced an increase in oxygen vacancies during the synthesis process, thereby reducing the step-free energy required for the final synthesis.